Dressing Method and Experiment of the Worm Grinding Wheel Tooth Profile based on the General Diamond Wheel - Yang Jianjun; Zhang Huiling; Tian Shuai; Liu Wei (Jixie chuandong)
While generating grinding the modification cylindrical gear,the special diamond wheel is used as a tool to dress the tooth profile of worm grinding usually.The diamond wheel is selected according to the different modification parameters of gear.The diamond wheel with arch edge is used as dressing tool for worm grinding wheels with different profile parameters.The dressing route of the diamond wheel is planned.The machine tool model for dressing worm grinding wheel is established in VERICUT,and the dressing simulation is proceeded also.In the end,the grinding experiments of modification gear and the gear surface measurement are carried out,which illustrated that the dressing method for worm grinding wheel is correct and feasible.